2023
DOI: 10.1371/journal.pone.0283123
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and demographics of slipped capital femoral epiphysis in South Korea: A nationwide cohort study

Abstract: Background This study investigated the epidemiology and demographics of slipped capital femoral epiphysis (SCFE) in South Korea using a nationwide population-based database. Methods Information on sex, age at onset, endocrine comorbidities, history of growth hormone therapy, history of radiation therapy, surgical methods, and complications in patients with SCFE aged younger than 18 years between 2007 and 2019 was retrieved from the Korean Health Insurance Review and Assessment Service database. Results Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Slipped capital femoral epiphysis (SCFE) is a complication of the proximal femur commonly seen in adolescents. It is defined as the displacement of the metaphysis relative to the epiphyses 1 A previous study regarding SCFE in the Asian population indicated that the incidence in children 9 to 14 years of age was 6.0/100,000, 2 with obesity and puberty being important risk factors. 3 In recent years, endocrine disorders such as hypothyroidism, hyperparathyroidism, hypogonadism, and hypopituitarism have increasingly been reported as causes of SCFE.…”
Section: Introductionmentioning
confidence: 99%
“…Slipped capital femoral epiphysis (SCFE) is a complication of the proximal femur commonly seen in adolescents. It is defined as the displacement of the metaphysis relative to the epiphyses 1 A previous study regarding SCFE in the Asian population indicated that the incidence in children 9 to 14 years of age was 6.0/100,000, 2 with obesity and puberty being important risk factors. 3 In recent years, endocrine disorders such as hypothyroidism, hyperparathyroidism, hypogonadism, and hypopituitarism have increasingly been reported as causes of SCFE.…”
Section: Introductionmentioning
confidence: 99%